Cerium(iv) ammonium nitrate mediated 5-endo-dig cyclization of α-amino allenylphosphonates to spirodienones1. Issue 17 (28th February 2015) - Adler, Pauline; Fadel, Antoine; Rabasso, Nicolas
<x xml:space="preserve">Abstract</x> α-Amino allenylphosphonates were treated with cerium(iv) ammonium nitrate under various conditions to form spirodienones in good to excellent yields.